2(x+3/4)=9(1/6-x)

Simple and best practice solution for 2(x+3/4)=9(1/6-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3/4)=9(1/6-x) equation:


2(x+3/4)=9(1/6-x)

We simplify the equation to the form, which is simple to understand
2(x+3/4)=9(1/6-x)

Reorder the terms in parentheses
+(+2x+1.5)=9*( + 0.16666666666667-x)

Remove unnecessary parentheses
+2x+1.5=+9+*( + 0.16666666666667-x+)

Reorder the terms in parentheses
+2x+1.5=+(+1.5-9x)

Remove unnecessary parentheses
+2x+1.5=+1.5-9x

We move all terms containing x to the left and all other terms to the right.
+2x+9x=+1.5-1.5

We simplify left and right side of the equation.
+11x=0

We divide both sides of the equation by 11 to get x.
x=0

See similar equations:

| -8x+9x+6=9 | | 6x-8x+2=-13 | | 35=x+(2x-1)+(3(2x-1)+3) | | 35=x+(2x-1)+(3(2x-1)+2) | | 35=x+(3x-1)+(4(3x-1)+2) | | x(x+5)+1=(x+6)(x+6) | | 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 | | 5x+9-4x=-1 | | 5x-1=4x-4 | | 6+3a+4a=-8 | | 5x-1=4x-1 | | 3x+9-2x=5 | | 440.2908=105.5668+25.748h | | 5-2[3x-4(5-x)]=6(7-x) |

Equations solver categories